2021
DOI: 10.1016/j.jare.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Update on systemic treatment for newly diagnosed inflammatory breast cancer

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…cN1-2 eligible if T size ≥1.5 cm. 3 , high risk breast cancer was defined as cT4/anyN/M0, any cT/N2-3/M0, or cT1-3/N0-1/M0, with RD. Patients with clinical stage cT1mi/T1a/T1b/N0 at disease presentation are not eligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cN1-2 eligible if T size ≥1.5 cm. 3 , high risk breast cancer was defined as cT4/anyN/M0, any cT/N2-3/M0, or cT1-3/N0-1/M0, with RD. Patients with clinical stage cT1mi/T1a/T1b/N0 at disease presentation are not eligible.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care for HER2+ IBC is a combined multimodality approach, that includes neoadjuvant therapy with dual anti-HER2 antibodies and anthracyclinebased chemotherapy with AC-THP (doxorubicin and cyclophosphamide, followed by paclitaxel or docetaxel with trastuzumab and pertuzumab) or non-anthracycline based chemotherapy with TCHP (docetaxel or paclitaxel, carboplatin, trastuzumab, and pertuzumab), followed by surgery, radiotherapy, and adjuvant systemic therapy (3)(4)(5)(6)(7)(8). Although the optimal neoadjuvant chemotherapy backbone with dual HER2 blockade for IBC patients is not well-established, regimens that omit anthracyclines, such as TCHP, have been used progressively more often on the basis of similar pathological complete response (pCR) and event-free survival rates; these regimens are associated with lower rates of cardiac toxicity and a lower risk of developing acute myeloid leukemia and myelodysplastic syndrome (5,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Among the BC subtypes, triple-negative (TN) IBC accounts for 20% to 40% of all IBC cases, and within this subtype, ~30% present with lymph node and distant metastasis at diagnosis and have the poorest prognosis [ 3 , 4 ]. Anthracycline–taxane-based chemotherapy remains the backbone of neoadjuvant therapy for TN IBC; however, the efficacy of this treatment is poor, with a dismal 15-year survival rate of ~20–30% [ 5 , 6 , 7 ]. The lack of effective therapies against TN IBC is due, in part, to a lack of clinical trials because (1) TN IBC is a different clinical and molecular entity than TN non-IBC, which causes the exclusion of TN IBC patients from most clinical trials [ 8 , 9 , 10 ] and (2) IBC is rare, making patient recruitment difficult for specific TN IBC clinical trials.…”
Section: The Clinical Burden Of Ibcmentioning
confidence: 99%
“…IBC is highly metastatic, and despite deploying a multidisciplinary approach to tackle this disease, the current anthracycline–taxane approach is minimally effective, with a very low 15-year survival rate of ~20–30% [ 5 , 6 , 7 ]. In other words, IBC patients do not have the luxury of waiting until efficacious therapies are found.…”
Section: The Urgency Of Applying Novel Efficacious and Economically A...mentioning
confidence: 99%
“…NACT with dual anti-HER2 antibodies (HP) is a standard regimen for HER2+ IBC based on multiple clinical data (14,29). In the TRYPHAENA study (30,31) reported the non-anthracycline regimen for 6 cycles [docetaxel, carboplatin, trastuzumab and pertuzumab (TCHP) regimen] had the promising highest pCR rate of 66.2% compared with 57.3-61.6% of anthracycline containing regimens for 6 cycles (FEC followed by docetaxel regimen).…”
Section: Systemic Treatment For Neoadjuvant Her2+ Ibcmentioning
confidence: 99%